Akurasi Arah Kiblat Masjid Dan Makam Di Kecamatan Tamalatea Dan Rumbia Kabupaten Jeneponto - Reski Ananda Saenab; Halim Talli; Rahma Amir (HISABUNA: Jurnal Ilmu Falak, 2023)
This study examines two main issues, namely the method of measuring the Qibla direction used by the people of the Tamalatea and Rumbia Subdistricts, the accuracy of the Qibla direction for mosques and tombs at the village level in Tamalatea and Rumbia Districts, Jeneponto Regency. This type of research is categorized as field research, then data collection techniques are interviews and documentation. The research methodology uses the Qiblat Tracker method based on Sun Compass and the Google Earth application. So the results of this study show that of the 14 mosques and 5 cemeteries that have measured the Qibla direction, only 1 mosque has the correct Qibla direction. The cause of the deviation of the mosque and the tomb is because the people in the Districts of Tamalatea and Rumbia still use the method of looking at the cardinal directions, setting the sun and also a compass. The implication of this research is the need for socialization to provide understanding to people who are still unfamiliar with the knowledge of astronomy, especially in the Qibla direction in theory and in terms of using the Qiblat Tracker method based on Sun Compass and Google Eart